Autophagy Induces Prosenescent Changes in Proximal Tubular S3 Segments - Baisantry, Arpita (J Am Soc Nephrol, 2016)
Evidence suggests that autophagy promotes the development of cellular senescence. Because cellular senescence contributes to renal aging and promotes the progression from AKI to CKD, we investigated the potential effect of tubular autophagy on senescence induction. Compared with kidneys from control mice, kidneys from mice with conditional deletion of autophagy-related 5 (Atg5) for selective ablation of autophagy in proximal tubular S3 segments (Atg5(Δ)(flox/)(Δ)(flox)) presented with significantly less tubular senescence, reduced interstitial fibrosis, and superior renal function 30 days after ischemia/reperfusion injury. To correlate this long-term outcome with differences in the early injury process, kidneys were analyzed 2 hours and 3 days after reperfusion. Notably, compared with kidneys of control mice, Atg5(Δ)(flox/)(Δ)(flox) kidneys showed more cell death in outer medullary S3 segments at 2 hours but less tubular damage and inflammation at day 3. These data suggest that the lack of autophagy prevents early survival mechanisms in severely damaged tubular cells. However, if such compromised cells persist, then they may lead to maladaptive repair and proinflammatory changes, thereby facilitating the development of a senescent phenotype and CKD.